PENGARUH BAURAN PROMOSI TERHADAP PEMBENTUKAN CITRA WISATA BUDAYA BERASTAGI KABUPATEN KARO PROVINSI SUMATERA UTARA - Zumri Sulthony (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
Recently the local government make promotion mix through advertising, sales promotion, public relations, direct sales and personal selling but in this study as the promotional mix is limited research on the topic of advertising and sales promotion. The method used in this research is descriptive research method in which data collection techniques used were through interviews, observations, questionnaires and library research. From the data processing questionnaires showed that the message contained in the form brosur, CD promotional tools (advertising) and exhibition (sales promotion) has been good, but the selection of the source of the message and not put in the proper distribution of promotional tools. Promotion mix that implemented by government of Karo is significant effect on the image of Berastagi as a cultural tourism destination in Karo District, North Sumatra Province. Then to test the coefficient of determination, showed that advertising and sales promotion influence the dependent variable that is the image of 58.80%. This means that 58.80% of Berastagi image as a cultural attraction influenced / is explained by the variables of advertising and sales promotion, while the remaining 41.20% is influenced / explained by other variables that are not included in this study.